2021
DOI: 10.21203/rs.3.rs-299979/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tensile properties of the FFF-processed thermoplastic polyurethane (TPU) elastomer

Abstract: Fused filament fabrication (FFF) has become one of the most popular, practical, and low-cost additive manufacturing techniques for fabricating geometrically-complex thermoplastic polyurethane (TPU) elastomer. However, there are still some uncertainties concerning the relationship between several operating parameters applied in this technique and the mechanical properties of the processed material. In this research, the influences of extruder temperature and raster orientation on the mechanical properties of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…This results in an uneven plastic deformation distribution throughout the surface for extruded AZ31. SMATs were run for longer periods at 40 min [20] and 20 min [53], and it is found that regardless of material, longer SMAT treatment leads to lower SR due to overlapping adjacent impact craters. [20,33,34,53], (b,c) surface topography due to media indents [31,35], (d) hardness [20,35,54,55] and (e) residual stress [56] of Mg alloys.…”
Section: Surface Integrity Of Smatmentioning
confidence: 99%
See 3 more Smart Citations
“…This results in an uneven plastic deformation distribution throughout the surface for extruded AZ31. SMATs were run for longer periods at 40 min [20] and 20 min [53], and it is found that regardless of material, longer SMAT treatment leads to lower SR due to overlapping adjacent impact craters. [20,33,34,53], (b,c) surface topography due to media indents [31,35], (d) hardness [20,35,54,55] and (e) residual stress [56] of Mg alloys.…”
Section: Surface Integrity Of Smatmentioning
confidence: 99%
“…SMATs were run for longer periods at 40 min [20] and 20 min [53], and it is found that regardless of material, longer SMAT treatment leads to lower SR due to overlapping adjacent impact craters. [20,33,34,53], (b,c) surface topography due to media indents [31,35], (d) hardness [20,35,54,55] and (e) residual stress [56] of Mg alloys. [20,33,34,53], (b,c) surface topography due to media indents [31,35], (d) hardness [20,35,54,55] and (e) residual stress [56] of Mg alloys.…”
Section: Surface Integrity Of Smatmentioning
confidence: 99%
See 2 more Smart Citations
“…The properties of workpiece (like hardness, morphology and roughness) after abrasive blasting are determined by blasting media used during process. [2] Usually, after adequately prepared surface, different methods of coatings are applied to base material in order to protect it against degradation.…”
Section: Introductionmentioning
confidence: 99%